Human cells and cell membrane molecular models are affected in vitro by the nonsteroidal anti-inflammatory drug ibuprofen (2011)
ABSTRACT: This report presents evidence that ibuprofen interacts with red cell membranes as follows: a) in scanning electron microscopy (SEM) studies on human erythrocytes induced shape changes at a concentration as low as 10μM; b) in isolated unsealed human erythrocyte membranes (IUM) induced mild increase in the water content or in their molecular dynamics at the hydrophobic-hydrophilic interphase, while a corresponding ordering decrease at the deep phospholipids acyl chain level; c) at physiological temperature (37°C), 300μM ibuprofen induced a significant increase in the generalized polarization (GP) of dimyristoylphosphatidylcholine (DMPC) large unilamellar vesicles (LUV), an indication that ibuprofen molecules locate in the head polar group region of DMPC; d) X-ray diffraction studies showed that ibuprofen concentrations≥300μM induced increasing structural perturbation to DMPC bilayers; e) differential scanning calorimetry (DSC) data showed that ibuprofen was able to alter the cooperativity of DMPC phase transition in a concentration-dependent manner, to destabilize the gel phase and that ibuprofen did not significantly perturb the organization of the lipid hydrocarbon chains. Additionally, the effect on the viability of both human promyelocytic leukemia HL-60 and human cervical carcinoma HeLa cells was studied.